Institutional innovation and forest landscape restoration in China: Multi-scale cross-sector networking, household fiscal modernization and tenure reform - Zhang, Kun.; Putzel, L. (Elsevier, 2016)
From 1999, China launched the Conversion of Cropland to Forest Program, an expansive forest landscape restoration project engaging 17% of the rural population in tree planting and management on ca. 30 million ha of degraded land and farmland in vulnerable watersheds. We describe the emergence of innovative institutions, horizontally and vertically networked from central to village government scales, articulating forestry with planning, finance, land, agriculture and water sectors. Compensation to participating households in grain was replaced by direct electronic cash transfers, promoting household fiscal modernization and inclusive finance. Compensation based on the area of household forest plots has reinforced tenure reforms and associated certifications.